Intravenous Tranexamic Acid in Implant-Based Breast Reconstruction Safely Reduces Hematoma without Thromboembolic Events. Issue 2 (August 2020) - Weissler, Jason M.; Banuelos, Joseph; Jacobson, Steven R.; Manrique, Oscar J.; Nguyen, Minh-Doan T.; Harless, Christin A.; Tran, Nho V.; Martinez-Jorge, Jorys
Abstract : Background: Antifibrinolytic medications, such as tranexamic acid, have recently garnered increased attention. Despite its ability to mitigate intraoperative blood loss and need for blood transfusion, there remains a paucity of research in breast reconstruction. The authors investigate whether intravenous tranexamic acid safely reduces the risk of hematoma following implant-based breast reconstruction. Methods: A single-center retrospective cohort study was performed to analyze all consecutive patients undergoing immediate two-stage implant-based breast reconstruction following mastectomy between 2015 and 2016. The incidence of postoperative hematomas and thromboembolic events among all patients was reviewed. The patients in the intervention group received 1000 mg of intravenous tranexamic acid before mastectomy incision and 1000 mg at the conclusion of the procedure. Fisher's exact test and the Mann-Whitney-Wilcoxon test were used. Multivariate logistic regression models were performed to study the impact of intravenous tranexamic acid after adjusting for possible confounders. Results: A total of 868 consecutive breast reconstructions (499 women) were reviewed. Overall, 116 patients (217 breasts) received intravenous tranexamic acid, whereas 383 patients (651 breasts) did not. Patient characteristics and comorbidities were similar between the two the groups. Patients who received tranexamic acid were less likely to develop hematomas [ n = 1 (0.46 percent)] than patients who did not [ n = 19 (2.9 percent)] after controlling for age, hypertension, and type of reconstruction (prepectoral and subpectoral) ( p = 0.018). Adverse effects of intravenous tranexamic acid, including thromboembolic phenomena were not observed. Multivariate analysis demonstrated that age and hypertension independently increase risk for hematoma. Conclusions: Intravenous tranexamic acid safely reduces risk of hematoma in implant-based breast reconstruction. Further prospective randomized studies are warranted to further corroborate these findings. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.